'Philip Payton: Cultural Entrepreneur for a Rhetorically Defined Space'. (1st May 2013) - Spriggs, Matthew
This article evaluates the editor, Philip Payton's, contribution to the field, and marks a wider 'coming of age' within Cornish studies as a whole. Cornish Studies became the vehicle for the 'New Cornish Studies' and its twin progeny (as Bernard Deacon once described them), the 'new Cornish historiography' and the 'new Cornish social science'. Privileging issues of Cornish identity, 'New Cornish Studies' sought to escape the narrow confines of antiquarian local history and to create instead an interdisciplinary, international, comparative inquiry that would both learn from and contribute to broader academic debates across the academy. Matthew Spriggs argues in this article that the relevance of a Cornish studies perspective is now abundantly clear.